Multilevel Annotation of Germline MEN1 Variants of Synonymous, Nonsynonymous, and Uncertain Significance in Indian Patients With Sporadic Primary Hyperparathyroidism. (17th August 2022) - Kaur, Gurjeet; Bhadada, Sanjay Kumar; Santra, Mithun; Pal, Rimesh; Sarma, Phulen; Sachdeva, Naresh; Dhiman, Vandana; Dahiya, Divya; Saikia, Uma Nahar; Chakraborty, Anuradha; Sood, Ashwani; Prakash, Mahesh; et al.
ABSTRACT: Primary hyperparathyroidism (PHPT) is third most common endocrine disorder characterized by hypercalcemia with elevated or nonsuppressed parathyroid hormone levels by parathyroid tumors. Familial PHPT, as part of multiple endocrine type‐1, occurs due to the germline mutation in the MEN1 gene. The involvement and the role of germline MEN1 variations in sporadic PHPT of Indian PHPT patients are unknown. Precise classifications of different types of MEN1 variations are fundamental for determining clinical relevance and diagnostic role. This prospective cohort study was performed on 82 patients with PHPT (with no clinical or history of MEN1 ) who underwent screening for MEN1 variations through Sanger sequencing. Multilevel computational analysis was performed to determine the structure–function relationship of synonymous, nonsynonymous, and variants of uncertain significance (VUS). Of the 82 PHPT patients, 42 (51%) had 26 germline MEN1 variants, including eight nonsynonymous, seven synonymous, nine VUS, one splice site, and one regulatory variation. Five most common germline variations (c.1838A>G, c.1817C>T, c.1525C>A, c.‐35A>T, and c.250T>C) were observed in this study. c.‐35A>T (5′ untranslated region [UTR]) was associated with recurrence of PHPT (odds ratio [OR] = 5.4; p  = 0.04) and subsequent detection of other endocrine tumors (OR = 13.6, p  = 0.035). c.1525C>A was associated with multi glandular parathyroid tumor (OR = 13.6, p  = 0.035). Align–Grantham variation and Grantham deviation (Align‐GVGD), functional analysis through hidden Markov MODEL (FATHMM), and MutationTaster analysis reported the disease‐specific potential of VUS and synonymous variations. Significant linkage disequilibrium was observed in c.1785G>A and c.1817C>T ( r 2  = 0.3859, p  = 0.0001), c.1475C>G and c.1525C>A ( r 2  = 0.385, p  = 0.0004), and c.1569T>C and c.1838A>G ( r 2  = 0.488, p  = 0.0001). The detection of MEN1 variations, especially those with disease‐specific potential, can prompt early screening for other MEN1‐related tumors and disease recurrence. © 2022 American Society for Bone and Mineral Research (ASBMR).